Improving Waste Bank Management Performance in Padang Pariaman - Humaira Humaira; Fanny Laura; Rika Idmayanti; Rasyidah Rasyidah; Fazrol Rozi (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2021)
The Nazhafa Garbage Bank is part of a Municipally owned corporation called BUMnag Pekandangan Emas, Padang Pariaman City. Cash data processing is still written in a book and MS Excel files. This resulted in the data not being recorded optimally. It takes long time to search for data, process transaction data and sometimes late payment of salaries to officers. Therefore, an information system for cash receipts and disbursements and remuneration was built at the Nazhafa Garbage Bank. This information system is built using codeigniter framework and MySQL DBMS. The final result is an information system that processes cash and salary data. With this system, you can record sales, record purchases, and record salaries every day or every month. This system can minimize the possibility of errors in data. This system improves the management performance of the Nazhafa Waste Bank. Bank Sampah Nazhafa merupakan bagian dari badan usaha milik nagari atau disingkat dengan BUMnag Pakandangan Emas Kota Padang Pariaman. Pengolahan data kas masih ditulis dalam buku agenda, memerlukan waktu lama untuk mencari data, mengolah data transaksi pada data penerimaan dan pengeluaran kas, dan pemberian gaji ke pegawai. Sistem informasi penerimaan dan pengeluaran kas serta penggajian dibangun untuk mengelola data penerimaan kas dan pengeluaran kas serta penggajian pada Bank Sampah Nazhafa. Sistem ini menggunakan framework codeigniter dan DBMS MySQL. Hasil akhir didapati sebuah sistem informasi yang melakukan pengolahan data kas dan data gaji, mendata penjualan, mendata pembelian, dan mendata gaji setiap hari ataupun setiap bulannya. Sistem ini meningkatkan kinerja pengelolaan pada Bank Sampah Nazhafa.